2020
DOI: 10.1101/2020.07.07.191064
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A developmental stretch-and-fill process that optimises dendritic wiring

Abstract: AbstractThe way in which dendrites spread within neural tissue determines the resulting circuit connectivity and computation. However, a general theory describing the dynamics of this growth process does not exist. Here we obtain the first time-lapse reconstructions of neurons in living fly larvae over the entirety of their developmental stages. We show that these neurons expand in a remarkably regular stretching process that conserves their shape. Newly available space is fill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 14 publications
(59 citation statements)
references
References 45 publications
4
52
0
Order By: Relevance
“…Taken together, our results demonstrate that a specialised dendritic tree pattern that minimises wire can be obtained by the precise temporal arrangement of stochastic developmental programs. Interestingly, evidence can be found that similar stages and strategies may be preserved across different cell types (Richardson and Shen, 2019;Gao et al, 2000;Sugimura et al, 2003Sugimura et al, , 2007Baltruschat et al, 2020) and species (Yoong et al, 2019). The flexible usage of such self-organisational programs provides developmental resilience and robustness to perturbations in the growth medium (Hiesinger and Hassan, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Taken together, our results demonstrate that a specialised dendritic tree pattern that minimises wire can be obtained by the precise temporal arrangement of stochastic developmental programs. Interestingly, evidence can be found that similar stages and strategies may be preserved across different cell types (Richardson and Shen, 2019;Gao et al, 2000;Sugimura et al, 2003Sugimura et al, , 2007Baltruschat et al, 2020) and species (Yoong et al, 2019). The flexible usage of such self-organisational programs provides developmental resilience and robustness to perturbations in the growth medium (Hiesinger and Hassan, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…C, Time courses of the total length of dendrite cable (left) and square root of the surface area (right) during development (see also Figure 6C). D, Scaling behaviour of the square root of the surface area against total length (left) and total length against number of branch points (right) showing the relationships expected from the optimal wire equations (Cuntz et al, 2012;Baltruschat et al, 2020). The dashed line shows the average scaling behaviour of simulated synthetic trees (n = 1, 000 simulations; see Methods).…”
Section: Fig 2 Quantification Of C1vpda Dendrite Differentiation Thrmentioning
confidence: 99%
See 3 more Smart Citations